The Anti-Inflammatory Potential of Tricyclic Antidepressants (TCAs): A Novel Therapeutic Approach to Atherosclerosis Pathophysiology - Eslami, Majid; Monemi, Marzieh; Nazari, Mohammad Ali; Azami, Mohammad Hossein; Shariat Rad, Parand; Oksenych, Valentyn; Naderian, Ramtin (Pharmaceuticals (Basel, Switzerland), 2025)
Atherosclerosis, a chronic inflammatory disease, is driven by complex molecular mechanisms involving inflammatory cytokines and immune pathways. According to recent research, tricyclic antidepressants (TCAs), which are typically prescribed to treat depressive disorders, have strong anti-inflammatory effects. TCAs, including imipramine and amitriptyline, alter inflammatory signaling cascades, which include lowering the levels pro-inflammatory cytokines like TNF-α, IL-1β, and IL-6 and inhibiting NF-κB activation. By inhibiting the NLRP3 inflammasome and suppressing pathways including JAK/STAT, MAPK, and PI3K, these effects are produced, improving endothelial function and reducing oxidative stress. The intricacy of TCAs’ anti-inflammatory actions has demonstrated by the existence of contradictory findings about how they alter IL-6 levels. The dependence of the heterogeneity of the reaction on the use of particular TCAs and experimental settings is shown by the fact that some studies show reduced IL-6 production, while others indicate increases or no changes. This review explores the multifaceted mechanisms through which TCAs modulate inflammatory pathways. TCAs inhibit NF-κB activation, reduce oxidative stress, and suppress the production of key inflammatory mediators, including IL-6 and TNF-α. They also regulate Toll-like receptor (TLR) signaling and NOD-, LRR-, and NLR family pyrin domain-containing protein 3 (NLRP3) inflammasome activation, reducing the release of IL-1β and IL-18, critical drivers of endothelial dysfunction and plaque instability. Given their capacity to target critical inflammatory molecules and pathways, TCAs provide great potential in the therapy of atherosclerosis, particularly for individuals with associated depression and cardiovascular risk factors. Nevertheless, further research is essential to clarify the precise molecular mechanisms, resolve inconsistencies in current findings, and establish the clinical applicability of TCAs as anti-inflammatory agents in atherosclerosis management.